The authentication and grading of edible bird's nest by metabolite, nutritional, and mineral profiling - Mohamad Ibrahim, Ramlah; Mohamad Nasir, Nurul Nadiah; Abu Bakar, Md Zuki; Mahmud, Rozi; Ab Razak, Nor Asma (MDPI AG, 2021)
Edible bird’s nest (EBN) produced by Aerodramus fuciphagus has a high demand for nutritional and medicinal application throughout the world. The present study was to evaluate the authentication of a man-made house EBN, which are half cup and stripe-shaped by FTIR. Next, both samples were compared according to their metabolite, nutritional, and mineral composition. The results indicated that the FTIR spectra of both EBN samples were identical and similar to the reference, suggesting the authenticity of the EBN used. The metabolites that contribute to the possible medicinal properties of EBN were found by using GC-MS. The results of the proximate analysis, followed by the standard AOAC method, inferred that both EBN shapes to be rich in crude protein and carbohydrate contents. However, the proximate composition between the half cup and stripe-shaped EBN showed significant differences. Major mineral elements detected were calcium and sodium, and magnesium contents were significantly different between both EBN. Additionally, the half cup and stripe-shaped EBN had a low level of heavy metal content than the maximum regulatory limit as set by the Malaysian Food Act 1983. This study concludes that the nutritional composition varied between the samples and thus suggests that nutrient content should be considered as criteria for the grading requirement of commercialized EBN.